PERSEPSI MASYARAKAT TERHADAP PERTUNJUKAN ORGEN TUNGGAL DALAM ACARA PESTA PERNIKAHAN DI KELURAHAN KUBU TANJUNG - Muhammad Luthfi; Yensharti (Universitas Negeri Padang, 2026)
This study aims to determine public perceptions of single organ performances at wedding receptions in Kubu Tanjung Village. The research method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. Therefore, this study is important to understand how the community interprets the existence of these performances. Informants in this study consisted of residents and community leaders selected by purposive sampling. The data obtained were then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The focus of this study covers three aspects of perception, namely sensory perception, social perception, and risk perception.